Patrząc na przemoc. Postawa, odczucia i bezsilność człowieka wobec okropności wojny w świetle retoryki okresu średniobizantyńskiego - Marinow Кirił (Vox Patrum, 2018)
The second and third decade of the 10th century was marked by an armed conflict between the East Roman Empire and Bulgaria. A conflict, which nearly brought about the downfall of Byzantium, was caused by ambitious plans of Symeon I (893-927), the Bulgarian ruler who desired to impose his supremacy upon the empire and gain new territories on the Balkan Peninsula at its cost. Only his death let the Byzantines take a breath and conclude a peace treaty with his son and follower, Peter I (927-969). Theodore Daphnopates (890/900 - after 961), the alleged author of a rhetoric work On the Treaty with the Bulgarians, praising the freshly concluded peace (in 927), reminded the atrocities of war. He also built up the image of a suffering human who had become a witness to the violence inflicted to the soil, temples and villages, as well as and first of all to humans during war operations. And although that image was in many aspects a cliché of the Byzantine literature through multiplying the images of suffering, present in other similar works, it referred to the deeply inrooted pattern of such feelings, based on the experience of many generations of Byzantines themselves and of the humankind in general. So, despite being a customary topos it reflected the possible or perhaps actual human experience of meeting with violence. In my presentation I will present and characterize the attitudes and emotions which accompanied the Byzantine author he had experienced (or at least said he had), being a witness and hearing the relations of atrocities of a fratricidal war.